2019
DOI: 10.4103/japtr.japtr_386_18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tribulus terrestris in mercuric chloride-induced renal accumulation of mercury and nephrotoxicity in rat

Abstract: Mercury generates free radicals and subsequently increases oxidative stress, which leads to renal injury. Tribulus terrestris (TT) has good anti-inflammatory and antioxidant properties. Hydroalcoholic extract of different dose of TT was evaluated against mercuric chloride-induced nephrotoxicity. Rats ( n = 6) were treated with TT at doses of 100, 200, and 300 mg/kg. Drugs were administered orally for 7 days. Single dose of mercuric chloride (5 mg/kg, intraperitonea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
(30 reference statements)
0
10
0
Order By: Relevance
“…HgCl 2 generates free radicals and subsequently increases oxidative stress, which leads to nephrotoxicity and accelerates hepatotoxicity [ 21 ]. This adverse effect of HgCl 2 could be eliminated by DPPD treatment probably because of its strong free radical scavenging activity through the electron(s) donation pathway, protecting cells from oxidation and necrosis [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…HgCl 2 generates free radicals and subsequently increases oxidative stress, which leads to nephrotoxicity and accelerates hepatotoxicity [ 21 ]. This adverse effect of HgCl 2 could be eliminated by DPPD treatment probably because of its strong free radical scavenging activity through the electron(s) donation pathway, protecting cells from oxidation and necrosis [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…T terrestris showed a protective kidney response in nephrotoxic rats. 33 M pruriens at the dose of 700 mg/kg b.wt show a protective response against arsenic-induced liver and kidney toxicity by reduced levels of kidney and liver enzymes. 34 A racemosus showed the kidney protective effect against alloxan induced diabetes rats.…”
Section: Discussionmentioning
confidence: 97%
“…The results showed that TT5 and TT10 increased ATP levels and decreased renal MDA, PAB, and MGMT in rats, with a greater effect observed in the TT10 group compared with TT5. The main protective effect of TT against nephrotoxicity may be related to the antioxidative effects of this plant, namely inhibiting the release of calcium and Cyt-C by reducing blood nitrogen-urea (BUN) and creatinine, reducing KIM-1 and liver fatty acid-binding protein (L-FABP), and increasing GSH expression (reduced glutathione), catalase, and SOD in renal tubules, which improve oxidative phosphorylation and increase ATP in renal tissue (27). Activation of p38 mitogen-activated protein kinase (MAPK) also leads to activation of nuclear respiratory factor (NRF)1/2 that leads to increased expression of DNA repairing genes (28).…”
Section: Discussionmentioning
confidence: 99%